Educating the Elite: A Social Justice Education for the Privileged Class - Wheeler-Bell, Quentin (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2017)
America is witnessing a new gilded age. Since the 1970’s, inequality in wealth and income has soared within the United States—and globally (Sayer, 2016; Therborn, 2013).  Such inequalities affect human flourishing because they allow the privileged class to convert their wealth into different, and unequal, lifestyles and life chances. In addition, such inequalities provide the privileged class with greater opportunity to convert their wealth, income, and social capital into influence within the political system that undermines democracy. Considering the vast class-based inequities, then, how can social justice educators help the students born into the world of class privilege understand their civic obligations to deepen democracy—particularly economic democracy? And, how can they do so without engaging in morally reprehensible teaching practices? This paper takes a ‘critical approach’ in attempting answer this question. First by analyzing the cultural and structural causes of behind the world of class privilege—what I term the pathology of privilege. As well as, explaining how the pathology of privileges undermines democracy. Then I analyze four possible social justice approaches for the class privilege—class suicide; political apathy; civic volunteerism; and activist ally. I concluded by explaining why the activist ally approach is both a more crucial and morally appropriate approach for educating the elite about their responsibility to deepen democracy and advance justice.